2002
DOI: 10.1614/0890-037x(2002)016[0379:fafmbp]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Fumigant Alternatives for Methyl Bromide Prior to Turfgrass Establishment1

Abstract: Potassium azide (PA) (112 kg/ha), oxadiazon + 1,3-dichloropropene (1,3-D) (168 kg/ha + 140 L/ha), dazomet (392 kg/ha), dazomet + chloropicrin (392 + 168 kg/ha), dazomet + 1,3-D (392 kg/ha + 140 L/ha), iodomethane (IM) (336 kg/ha), metam-sodium (MS) (748 L/ha), MS + chloropicrin (748 L/ha + 168 kg/ha), and MS + 1,3-D (748 + 140 L/ha) were evaluated at Jay and Arcadia, FL, in 1998 and 1999 as alternatives to methyl bromide (MeBr) fumigation for the management of common turfgrass weeds. Potassium azide was as eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 9 publications
4
33
1
Order By: Relevance
“…The same authors also noted that MeI produced similar control of the pest to a combination of 1,3-dichloropropene with 17% chloropicrin (essentially the commercial product, Telone C-17). Unruh et al (2002) found that MeI controlled weedy grass species, sedge species, and broadleaf weeds present at two locations under differing environmental conditions. However, Webster et al (2001) noted that while MeI was effective in controlling purple nutsedge early in the growing season of a bell pepper-squash cropping sequence, by the end of the growing season, the MeI offered no advantage over a control.…”
Section: Quantifying Exposure Of Plant Pests To Meimentioning
confidence: 98%
“…The same authors also noted that MeI produced similar control of the pest to a combination of 1,3-dichloropropene with 17% chloropicrin (essentially the commercial product, Telone C-17). Unruh et al (2002) found that MeI controlled weedy grass species, sedge species, and broadleaf weeds present at two locations under differing environmental conditions. However, Webster et al (2001) noted that while MeI was effective in controlling purple nutsedge early in the growing season of a bell pepper-squash cropping sequence, by the end of the growing season, the MeI offered no advantage over a control.…”
Section: Quantifying Exposure Of Plant Pests To Meimentioning
confidence: 98%
“…(Gilreath et al, 2005;Chase et al, 2006), Ipomoea sp., and several other annual weeds such as Amaranthus retroflexus L. (Unruh et al, 2002), but was weak against Cynodon dactylon L. Pers. and Mollugo verticillata L. (Unruh et al, 2002). A commercial formulation of 1,3-D (61%) + chloropicrin (33%) also has been tested as a MeBr replacement.…”
Section: Introductionmentioning
confidence: 97%
“…Iodomethane controlled several grass weed species, sedges, and broadleaf weeds in turf (Unruh et al, 2002). Zhang et al (1997) reported good control of A. retroflexus with iodomethane and found that it was more potent than MeBr on Lolium multiflorum Lam., Abutilon theophrasti Medik., Chenopodium album L., P. oleracea, Brassica kaber (DC.)…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has indicated several fumigants or fumigant combinations have the potential to be used as methyl bromide alternatives in weed control. Nevertheless, very few performed as well as methyl bromide, especially for bermudagrass control, and problems stated above about the fumigation process still exist (8,15).…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the toxic and volatile nature of most liquid fumigants, preplant fumigation can be both expensive and hazardous. Equipment limitations, toxicity issues, potential ground water contamination, personal protective equipment (PPE) requirements, and high summer temperatures of the Southeast can render this practice nearly impossible (15).…”
Section: Introductionmentioning
confidence: 99%